Design and Execute a Complete Vehicle System for the MOHEDSR - Mead Ali Moter; Rafah Al-Hamdani; Israa Shehab; Wasan Ala'a alhamami (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Databases touch all aspects of our lives. The database is a group of records that is arranged in a way that makes it easy to be managed, accessed and updated. The relational database can be defines as a group of data items arranged as a set of formally-described tables. Data can be accessed and reassembled in a number of different ways without having to reorganize the database tables. The Ministry of higher education and scientific research currently stores the vehicles records manually this makes it hard and difficult to manage and update these records. This project aims to develop a database management system to store and retrieve the vehicles records of the ministry of the higher education. The project’s system are developed using Oracle database management software, the system provides an interface for the data entry of a new vehicle record. Updating data of a previously added record is also performed using interfaces. SQL has been used in developing the system queries to display reports and tables based on specified constrains.